2020
DOI: 10.1177/0954406220922257
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and free vibration properties of skin and core designed basalt woven intertwined with flax layered polymeric laminates

Abstract: Design of fiber-reinforced polymer damping laminates has been attracting great interest in industrial sectors for lightweight structural damping applications. The present work investigates the impact of skin, core, neutral, and alternate intertwined basalt/flax fabric on the mechanical and vibrational properties of the newly designed polymeric laminate. The designed sequence structure was fabricated using a wet hand lay-up technique with hydraulic compression. Tensile and flexural strength of intertwined multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…Contrary results have also been reported in the latest literature [106] for hybrid composites made of basalt and flax woven fabrics (0/90 orientation). Authors observed that the maximum damping is obtained when basalt is in the outer layer [106,107].…”
Section: Stacking Sequencecontrasting
confidence: 91%
See 2 more Smart Citations
“…Contrary results have also been reported in the latest literature [106] for hybrid composites made of basalt and flax woven fabrics (0/90 orientation). Authors observed that the maximum damping is obtained when basalt is in the outer layer [106,107].…”
Section: Stacking Sequencecontrasting
confidence: 91%
“…Y. Li et al find the damping properties in hybrid composites (flax and carbon fiber) are greatly influenced by the position of the flax fiber layers, which are supposed to dissipate more energy than those with synthetic fibers in fiber direction [45]. Contrary results have also been reported in the latest literature [106] for hybrid composites made of basalt and flax woven fabrics (0/90 orientation). Authors observed that the maximum damping is obtained when basalt is in the outer layer [106,107].…”
Section: Stacking Sequencementioning
confidence: 92%
See 1 more Smart Citation
“…Table 1 presents the physical and mechanical characteristics of chosen materials from references. 7,36 The thickness of Ti sheet, basalt, and flax fiber are 0.5, 0.24,…”
Section: Fiber Treatmentsmentioning
confidence: 99%
“…4 The common configuration schemes that were used by researchers are (1) metal and fiber, (2) fiber and metal, and (3) interplyed of a single fiber or multiple fiber layers between metal sheets. In addition to the above configurations, the various fibers are alternatively plied to improve MFLs properties that include damping flax (F) 5,6 and high-strength basalt (B) 7 layers between Ti sheets, termed as Ti/B/F/B/F/B/Ti MFL which has been considered in the current investigation. They notably increase the internal dissipation of shock energy of Ti MFL as well as its tensile strength.…”
Section: Introductionmentioning
confidence: 99%